Missed Volar Intercalated Segment Instability with Distal Radius Fracture: Challenges in Diagnosis, Surgical Management, and Clinical Outcome - Case Report - Abdelrahman Mustafa-Kamel Alfarra; Saeda Albarawi (Journal of Orthopaedic Case Reports)
Introduction: Advancements in radiology have enhanced the understanding of carpal instability and its biomechanics. Case Report: This case report discusses a 37-year-old male patient who suffered a distal radius fracture and subsequent volar intercalated segment instability (VISI). Despite being less common than other forms of carpal instability, VISI presents clinical significance. Initial evaluations post-fracture did not identify the instability. After identifying VISI, an open reduction and internal fixation procedure with Luno-Triquetral Fusion and bone grafting was performed. Post-operative immobilization aided successful fusion and enhanced wrist stability. Follow-up showed symptom improvement, increased range of motion, and improved hand function. Conclusion: This study underscores the importance of diagnosing and addressing lesser-known carpal instability patterns, emphasizing careful clinical assessments, advanced radiology, appropriate surgical and physical therapy interventions, and vigilant follow-up.